The age of training regulations as an indicator for the need for modernisation of recognised training occupations? : Work report from a BIBB research project - Blankart, Stephanie [Verfasser]; Schad-Dankwart, Inga [Verfasser]; Bretschneider, Markus [Verfasser] (My University, 2022)
"Recognised training occupations act as a guarantee that qualified skilled workers will develop a professional capacity and in consequence employability skills in training. Occupational qualifications are subject to constant change and need to be adjusted to altered circumstances. But which factors trigger the update of training regulations? And what role is played by aspects such as the age of the regulations in question? This article uses the initial results from an ongoing BIBB research project to show which possible factors may be considered with regard to designing indicators for systematic monitoring of the modernisation requirements of initial and advanced training occupations." (authors' abstract; BIBB-Doku)
Keywords: S 2.2.1 Ordnung von Ausbildungsberufen; 370; Ausbildungsberuf; Neuordnung der Ausbildungsberufe; Indikatorenbildung; Einflussfaktor